البيئة اللغوية وتأثيرها في تحسين مهارة الكلام لطلبة الدراسات العليا في الدراسات العربية والإسلامية THE LINGUISTIC ENVIRONMENT AND ITS IMPACT ON IMPROVING THE SPEECH SKILLS OF POSTGRADUATE STUDENTS IN ARABIC AND ISLAMIC STUDIES - Ali, Asem Shehadeh Saleh; Muslim, Nadzri (media Printer, 2019)
تُعدّ اللغة العربيّة من أقدم اللغات المتداولة في العالم، تحدّث بها الناس منذ زمن قديم قبل بعثة نبيّنا محمد صلى الله عليه وسلم، وما زالت صامدةً إلى يومنا هذا، إلا أن العرب الأقحاح لم يُنقل عنهم اهتمامهم بالجانب التنظيري التقعيدي لقواعد اللغة عموماً، وإنّما كانوا يتكلّمون اللغة العربية من باب السليقة؛ أما البيئة اللغوية فهي أحد المداخل التعليمية التي تهدف إلى تحسين كفاءة مهارة الكلام لدى الدارس في اللغة الثانية بالاستفادة من البيئة بوصفها مصدرا للتعلم. سيتبع البحث المنهج الوصفي التحليلي، ويهدف إلى دراسة وتحليل مدى ملاءمة مهارة الكلام لدى الطلبة لمستواهم، ودراسة إسهام البيئة اللغوية في تحسين مهارة الكلام، ومعرفة مدى تأثير البيئة اللغوية في مهارة الكلام لدى الطلبة بالجامعة الإسلامية العالمية بماليزيا. The Arabic language is one of the oldest spoken languages in the world, spoken by people from a long time before the mission of our Prophet Muhammad, peace be upon him, and is still standing to this day, but the origin Arab not conveyed their interest in the basic theoretical side of the rules of language in general, but they were speaking Arabic language intutionality; the linguistic environment is one of the educational approaches aimed at improving the efficiency of the student's speaking skill as a second language by taking advantage of the environment as a source of learning. The research will follow the descriptive analytical approach, and aims to study and analyze the suitability of speech skill among students to their level, and study the contribution of the linguistic environment in improving speech skill, and to know the impact of the linguistic environment on the speech skill of students at the International Islamic University of Malaysia.